The Application of Aspects of Islamic Family Law to the Muslim Minority in Singapore: A Literature Review - Silawati; Aslati; Agustar, Armi; Zein, Anwar (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This article will discuss the position and application of Islamic family law in countries with Muslim minority populations, particularly in Singapore. In every Muslim community in the world, no one denies the existence of Islamic law with its universal character of application. The universality of the application of Islamic law requires the submission of all Muslims to the teachings of Islam, will not see the time and place not to implement its provisions, and also requires the existence of universal values contained in branch laws that may differ from one place to another. That is why Muslims in Islamic countries and countries where the majority of the population is Muslim have relatively no problems with the application of Islamic law in everyday life because Islam upholds religious tolerance. The above reality will undoubtedly be different if Islamic law develops among Muslims, who are a minority in secular countries, namely countries with a government system that separates religion as a private matter.